Violation of the Strategies of Conversation in Some English Selected Plays (Journal of the College of Languages (JCL), 2013)
The present study analyzes the violation of the strategies of conversation in two English plays namely Richard II and King Lear. The present study tries to achieve the following goals: 1. showing how the strategies of real conversation can be applied to conversation in plays. 2. analyzing how the characters communicate with each other to discover how Shakespeare violates the strategies of conversation in depicting his characters. The study has been conducted on the bases of the following hypotheses:The strategies of conversation which are derived from the study of natural conversation can be applied to conversation in drama with some modification for dramatic purposes.Shakespeare makes certain violations of the strategies of conversation especially in the state of insanity these strategies are discarded. Analytical procedure is followed for the investigation of the two plays. The study depends basically on Sacks et al.’s model (1974) for conversation structure, Duncan and Fiske (1977) for turn size, Grice’s Maxims (1975) and Brown and Levinson (1978) for conversation implicature.